2014
DOI: 10.1017/atsip.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Survey on securing data storage in the cloud

Abstract: Cloud Computing has become a well-known primitive nowadays; many researchers and companies are embracing this fascinating technology with feverish haste. In the meantime, security and privacy challenges are brought forward while the number of cloud storage user increases expeditiously. In this work, we conduct an in-depth survey on recent research activities of cloud storage security in association with cloud computing. After an overview of the cloud storage system and its security problem, we focus on the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 98 publications
(123 reference statements)
0
28
0
1
Order By: Relevance
“…In recent years, cloud computing and edge computing that use resourses of providers are rapidly spreading in many fields. However, there are some security concerns such as unauthorized use and leak of data, and privacy compromise [1]. For solving these privacy concerns for end-users, many researches has been conducted [2]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cloud computing and edge computing that use resourses of providers are rapidly spreading in many fields. However, there are some security concerns such as unauthorized use and leak of data, and privacy compromise [1]. For solving these privacy concerns for end-users, many researches has been conducted [2]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies on secure, efficient and flexible communications have been reported [1]- [3]. For securing multimedia data, full encryption with provable security (like RSA, AES, etc) is the most secure option.…”
Section: Introductionmentioning
confidence: 99%
“…With the wide/rapid spread of distributed systems for information processing, such as cloud computing and social networks, not only transmission but also processing is done on the public Internet, and thus contents are transmitted over an insecure bandwidth-constrained communication channel [1], [2]. In the meantime, a lot of studies on secure, efficient and flexible communications have been reported.…”
Section: Introductionmentioning
confidence: 99%